‘Can do’ versus ‘Do do’ in nursing home residents: identification of contextual factors discriminating groups with aligned or misaligned physical activity and physical capacity - Adams, Michael; Elser, Alexander; Fricke, Madeleine; Jaufmann, Lydia; Wollesen, Bettina; Muehlbauer, Thomas; Jansen, Carl-Philipp; Schwenk, Michael (European review of aging and physical activity, 2024)
Physical activity (PA) is fundamental to nursing home residents’ health. Likewise, physical capacity (PC) is essential to carry out activities of daily living. Although PC and PA are associated, misalignment has been reported in specific subgroups. Increased PC is oftentimes not linked to high PA (i.e., Can do - don’t do) and vice versa (i.e., Can’t do - do do). Therefore, identifying other contextual factors influencing PA in misaligned groups is important. This study aimed to identify contextual factors in nursing home residents with aligned or misaligned PA and PC.